Bahasa Perlawanan dan Politik Tubuh dalam Teori Drama Pasca-Kolonial Helen Gilbert dan Joanne Tompkins - Khurosan, Herpin Nopiandi; Yuliatin, Riyana Rizki (Universitas Hamzanwadi, 2020)
This paper is a review and preparation of concepts, ideas and theoris of post-colonial drama in Helen Gilbert andTompkinsÃ¢â‚¬â„¢s sense. I use Ã¢â‚¬Å“Post-Colonial Drama: Theory, Practice, PoliticsÃ¢â‚¬Â as a main source of their ideas about post-colonial Drama. I limited this paper in theories of canonical counter-discourse, the language of resistance, and body politics in post-colonial context. The result of this reconstruction to their theories is developed to become theoretical and methodological framework which can be used to analyse post-colonial drama in later researches.